Effects of morphine on coronary and left ventricular dynamics in conscious dogs. - Vatner, S F (1975)
We studied the effects of i.v. 2 mg/kg morphine sulfate (MS) on coronary blood flow and resistance, left ventricular (LV) diameter and pressure (P), rate of change of pressure (dP/dt), and dP/dt/P in conscious dogs. An initial transient reduction in coronary vascular resistance, associated with increases in heart rate, dP/dt, dP/dt/P, and reductions in LV end-diastolic and end-systolic size were observed. This was followed by a prolonged increase in mean coronary vascular resistance, lasting from 5 to 30 min, while heart rate, arterial pressure, and LV end-diastolic diameter returned to control levels and dP/dt/P remained slightly but significantly above control. At 10 min, late diastolic coronary flow had fallen from 44 plus or minus 3 ml/min to a minimum level of 25 plus or minus 3 ml/min, while late diastolic coronary resistance had risen from 1.68 plus or minus 0.10 to 3.04 plus or minus 0.28 mm Hg/ml/min. Morphine also induced substantial coronary vasoconstriction when heart rate was held constant. Neither the MS-induced coronary vasoconstriction nor the positive inotropic response was abolished by bilateral adrenalectomy. The positive inotropic response of MS was reversed after beta blockade, but not the coronary vasoconstriction. Alpha receptor blockade abolished the late coronary vasoconstriction effects of morphine, and only dilatation occurred. In anesthetized dogs MS failed to produce late coronary vasoconstriction. Coronary after a respiratory-depressant dose of morphine, 10 mg/kg i.v. Smaller doses of MS, 0.25 mg/kg every 15 min, produced significant coronary vasoconstriction after a total dose of 0.75 mg/kg in the conscious dogs. The effects of morphine may differ in the normal dog and man and may vary depending upon the presence or absence of coronary artery disease. However, in the normal conscious dog, MS elicits a mild beta adrenergic increase in contractility and an important coronary vasoconstrictor effect, which is mediated through alpha adrenergic receptors.